Translation and Validation of Edinburgh Handedness Inventory in Urdu Language for Cerebral Palsy - Faiqa Ramzan, Shoaib Waqas, Muhammad Waqas Ahmed, Muhammad Tariq, Atiqa Niamat, Hafiz Muhammad Asim , (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To translate and validate EHI in Urdu language. Methods: Non-probability convenient sampling approaches used in a descriptive cross-cultural validation research design. The study also included twenty parents of children with cerebral palsy and specialists in pediatric rehabilitation. An English professor or physician completed the back translation, while two separate multilingual translators translated EHI forward into Urdu. These translators were proficient in both Urdu and English. An expert panel committee created and approved the final version of EHI in Urdu. The consent of the guardian acquired beforehand, and confidentiality ensured. The SPSS version 21 used to input and analyzes the data, and a pretest sample of 150 people used1. Result: For reliability statistics, the mean age of participants was 40.4 with standard deviation of 15.994 and Cronbach alpha of EHI questionnaire after translation was 0.943 or after testing on parents of cerebral palsy patients was 0.964 andcontent validity also showed good content validity ratio which was 0.72. Pearson correlation showed an excellent test-retest reliability and internal consistency 0.946 and after testing intraclass correlation varied from 0.523 to 0.956-show high reliability respectively. Conclusion: The Urdu version of EHI is a valid and reliable tool for Urdu speaking population of Pakistan. Keywords: Cerebral palsy, Edinburgh handedness inventory, Ghurki trust teaching hospital, Lahore College of physical therapy